Hermeneutical Approaches in Psychology of Religion - Belzen, J.A., (International Series in the Psychology of Religion ;, 1997)
Contemporary psychology is reviving with new vigor an interest in hermeneutics, or the human science of interpretation. After a period in which positivistic and statistical approaches have been dominant, new methods are being explored. Most of these focus on narrative, cultural analysis, embodiment and interdisciplinarity. Because of its specific object of study, psychology of religion has never been without an hermeneutical emphasis. In this field of psychology scholarship, these new directions are especially welcomed as they offer perspectives for research which attempts to interpret religion as a human phenomenon. This volume presents hermeneutical psychological studies on religion which rely on both classical and contemporary approaches. Dealing with topics like mysticism, religious symbols, life stories and mental health, contributions to the volume draw on a variety of perspectives. These range from psychoanalysis, narrative psychology and feminism to perspectives drawn deep from the wellspring of interdisciplinary collaboration with anthropology and history.